(3BaGb GdJfejI h GdJcGed GdGbJUGOj Hjf Ohd THg GdLRjQI GdYQHjIs - (3LGSe Hf eMeO(B, (3GdbGSejs ((3YeGf(B:s (3eDSSI THGH GdLGeYI(B,s, 1999)
(3GdJfejI GdGbJUGOjI(B- (3GdJcGed GdGbJUGOj;GdSjGSI GdGbJUGOjI(B- (3GdHdGO GdYQHjI, THg GdLRjQI GdYQHjIs
Keywords: (3GdHdGO GdYQHjI (B- (3SjGSI GbJUGOjIs; (3THg GdLRjQI GdYQHjI (B- (3JcGed GbJUGOjs; (3THg GdLRjQI GdYQHjI (B- (3SjGSI GbJUGOjIs